2013
DOI: 10.3390/ijerph10115953
|View full text |Cite
|
Sign up to set email alerts
|

A General Model of Dioxin Contamination in Breast Milk: Results from a Study on 94 Women from the Caserta and Naples Areas in Italy

Abstract: Background: The Caserta and Naples areas in Campania Region experience heavy environmental contamination due to illegal waste disposal and burns, thus representing a valuable setting to develop a general model of human contamination with dioxins (PCDDs-PCDFs) and dioxin-like-PCBs (dl-PCBs). Methods: 94 breastfeeding women (aged 19–32 years; mean age 27.9 ± 3.0) were recruited to determine concentrations of PCDDs-PCDFs and dl-PCBs in their milk. Individual milk samples were collected and analyzed according to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…In recent decades, different studies have focused on the potential impact of illegal waste disposal on human health in the so-called "land of fires" in Campania (Altavista et al, 2004;Cembalo et al, 2019;Mazza et al, 2018Mazza et al, , 2015Pirastu et al, 2013;Rivezzi et al, 2013;Senior & Mazza, 2004;Zona et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, different studies have focused on the potential impact of illegal waste disposal on human health in the so-called "land of fires" in Campania (Altavista et al, 2004;Cembalo et al, 2019;Mazza et al, 2018Mazza et al, , 2015Pirastu et al, 2013;Rivezzi et al, 2013;Senior & Mazza, 2004;Zona et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, a dramatic example of this situation is represented by several municipalities of the provinces of Naples and Caserta, in the Campania region. Illegal dumping and burning of waste in this region have caused an immense environmental damage, which might have affected the local population's health (Altavista et al, 2004;Cembalo et al, 2019;Mazza et al, 2018;Mazza, Piscitelli, Neglia, Della Rosa, & Iannuzzi, 2015;Pirastu et al, 2013;Rivezzi et al, 2013;Senior & Mazza, 2004;Zona et al, 2019). These areas have been referred to as the "land of fires," owing to the common practice of waste burning (Mazza et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Six studies investigated the link between waste-related pollution and biomarkers assessment in humans. Two studies identified high dioxin levels in breast milk of 94 primiparae living in Naples and Caserta provinces, and detected a positive correlation with age of sampled women, illegal waste fires and environmental dioxin risk index (EDR), that is an index based on dioxins concentrations in buffalo milk samples [ 33 , 34 ]. Illegal waste fires appeared to be a more important determinant of dioxin exposure in milk for women living in an area at low risk compared to high risk areas.…”
Section: Resultsmentioning
confidence: 99%
“…In this context we have explored the expression of CYP1A1 in the acne lesions of 16 patients living in the region of Naples, Italy, where different epidemiological studies suggest an environmental contamination by dioxins [16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%